PENGUKURAN TINGKAT KEPUASAN MAHASISWA TERHADAP PROSES PENDIDIKAN BERBASIS METODE ERGO-SERVQUAL DI PTS ‘XYZ’ - Rinamurti, Micheline; Setiawan, Heri (Catholic University Musi Charitas, 2020)
Educational Criteria in Study Program / College Performance Reports and Self-Evaluation Reports on Study Program Accreditation Instruments v4.0, show that user satisfaction is an important aspect of the report structure. This study took data from a study on the satisfaction level of active students of XYZ class 2015-2019 from all study programs. This study uses the Ergo-ServQual method, and the Ergo (Ergonomics) method is used as an analytical tool to provide suggestions for improving student satisfaction levels. The level of satisfaction of XYZ students with the quality of services provided by the XYZ management / management Unit is currently not optimal, as evidenced by the Tangible dimension which is an attribute of the quality of student assessment services on adequacy, accessibility and quality of facilities and infrastructure that have not provided a high level of satisfaction. It needs critical thinking, creativity, and smart work with detailed and rational Key Performance Indicators (KPI